MUSEUMS AND QUALITY, FROM THE CONCEPT OF THE MUSEUM THAT CARRIES OUT FUNCTIONS TO THE MUSEUM THAT PROVIDES SERVICES (Cadernos de Sociomuseologia, 2009)
Quality management Self-evaluation of the organisation Citizens/customers satisfaction Impact on society evaluation Key performance evaluation Good practices comparison (Benchmarking) Continuous improvement  In professional environments, when quality assessment of museums is discussed, one immediately thinks of the honourableness of the directors and curators, the erudition and specialisation of knowledge, the diversity of the gathered material and study of the collections, the collections conservation methods and environmental control, the regularity and notoriety of the exhibitions and artists, the building’s architecture and site, the recreation of environments, the museographic equipment design. We admit that the roles and attributes listed above can contribute to the definition of a specificity of museological good practice within a hierarchised functional perspective (the museum functions) and for the classification of museums according to a scale, validated between peers, based on “installed” appreciation criteria, enforced from above downwards, according to the “prestige” of the products and of those who conceive them, but that say nothing about the effective satisfaction of the citizen/customers and the real impact on society. There is a lack of evaluation instruments that would give us a return of all that the museum is and represents in contemporary society, focused on being and on the relation with the other, in detriment of the ostentatious possession and of the doing in order to meet one’s duties. But it is only possible to evaluate something by measurement and comparison, on the basis of well defined criteria, from a common grid, implicating all of the actors in the self-evaluation, in the definition of the aims to fulfil and in the obtaining of results.